2017
DOI: 10.1063/1.4985558
|View full text |Cite
|
Sign up to set email alerts
|

Retrofitted green roofs and walls and improvements in thermal comfort

Abstract: Abstract. Increased urbanization has led to a worsening in the quality of life for many people living in large cities in respect of the urban heat island effect and increases of indoor temperatures in housing and other buildings. A solution may be to retrofit existing environments to their former conditions, with a combination of green infrastructures applied to existing walls and rooftops. Retrofitted green roofs may attenuate housing temperature. However, with tall buildings, facade areas are much larger com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Various studies have reported the efficiency of green roofs and walls in attenuating indoor temperatures 9,10,11,12 .…”
Section: Attenuation Of Indoor Temperature In Housing With Green Roofmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have reported the efficiency of green roofs and walls in attenuating indoor temperatures 9,10,11,12 .…”
Section: Attenuation Of Indoor Temperature In Housing With Green Roofmentioning
confidence: 99%
“…Wilkinson & Castiglia Feitosa 10 found temperatures as much as 14.8ºC lower in prototypes with retrofitted green roofing compared to those without green technology. Castiglia Feitosa & Wilkinson 12 also assessed the heat sensation in prototype buildings in Sydney, Australia, based on characterization of the risk of human exposure to heat according to the U.S. National Weather Service (NWS) 13 . The authors found that modular green systems fitted to walls and roofs were capable of reducing the proportion of extreme heat conditions (> 41ºC, categorized as "danger" and "extreme danger"), from 11.7% to only 0.4%.…”
Section: Attenuation Of Indoor Temperature In Housing With Green Roofmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertical greenery systems have shown their advantages in different climates, as green walls improve the thermal comfort of indoor environments, and can also reduce a building's energy consumption during the summer and winter seasons [27][28][29][30]. Moreover, the cooling load was reduced by 20% when plants were used as green walls instead of blinds under the same solar radiation intensities [31].…”
Section: Introductionmentioning
confidence: 99%